Eriodictyol can modulate cellular auxin gradients to efficiently promote in vitro cotton fibre development - Anam Qadir Khan; Zhonghua Li; Muhammad Mahmood Ahmed; Pengcheng Wang; Xianlong Zhang; Lili Tu (BMC Plant Biology, 2019)
Abstract Background Flavonoids have essential roles in flower pigmentation, fibre development and disease resistance in cotton. Previous studies show that accumulation of naringenin in developing cotton fibres significantly affects fibre growth. This study focused on determining the effects of the flavonoids naringenin, dihydrokaempferol, dihydroquerectin and eriodictyol on fibre development in an in vitro system. Results 20 μM eriodictyol treatment produced a maximum fibre growth, in terms of fibre length and total fibre units. To gain insight into the associated transcriptional regulatory networks, RNA-seq analysis was performed on eriodictyol-treated elongated fibres, and computational analysis of differentially expressed genes revealed that carbohydrate metabolism and phytohormone signaling pathways were differentially modulated. Eriodictyol treatment also promoted the biosynthesis of quercetin and dihydroquerectin in ovules and elongating fibres through enhanced expression of genes encoding chalcone isomerase, chalcone synthase and flavanone 3-hydroxylase. In addition, auxin biosynthesis and signaling pathway genes were differentially expressed in eriodictyol-driven in vitro fibre elongation. In absence of auxin, eriodictyol predominantly enhanced fibre growth when the localized auxin gradient was disrupted by the auxin transport inhibitor, triiodobenzoic acid. Conclusion Eriodictyol was found to significantly enhance fibre development through accumulating and maintaining the temporal auxin gradient in developing unicellular cotton fibres.